Aerosol Jet Printing for Neuroprosthetic Device Development - Lander De Waele; Massimo Di Pietro; Stefano Perilli; Emanuele Mantini; Giulio Trevisan; Michela Simoncini; Massimo Panella; Viviana Betti; Matteo Laffranchi; Dante Mantini (Bioengineering, 2025)
Aerosol jet printing (AJP) technology has emerged as a transformative tool in neuroprosthetic device development, offering high accuracy and versatility in fabricating complex and miniaturized structures, which are essential for advanced neural interfaces. This review explores the fundamental principles of AJP, highlighting its unique aerosol generation and concentrated deposition mechanisms, which facilitate the use of different materials on a variety of substrates. The advantages of AJP, including its device scalability, ability to print on flexible and stretchable substrates, and compatibility with a wide range of biocompatible materials, are examined in the context of neuroprosthetic applications. Key implementations, such as the fabrication of neural interfaces, the development of microelectrode arrays, and the integration with flexible electronics, are discussed, showcasing the potential of AJP to revolutionize neuroprosthetic devices. Additionally, this review addresses the challenges of biocompatibility and technical limitations, such as the long-term stability of electroconductive traces. The review concludes with a discussion of future directions and innovations, emphasizing the realization of sensorized prosthetic limbs through the incorporation of tactile sensors, the integration of biosensors for monitoring physiological parameters, and the development of intelligent prostheses. These prospects underscore the role of AJP in the advancement of neuroprosthetic applications and its pathway toward clinical translation and commercialization.